Cochrane Database of Systematic Reviews 2008
DOI: 10.1002/14651858.cd004241.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Medical interventions for fungal keratitis

Abstract: There is no evidence that the current available and investigational antifungal agents are effective. The review identified the need for large multicentre randomised trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
53
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 15 publications
0
53
0
2
Order By: Relevance
“…Although there is no gold standard for the treatment of fungal keratitis [1,6], the combination of systemic voriconazole and topical natamycin seems to represent one of the most commonly used antifungal treatment regimens. This correlates with results of the MUTT 1 trial from South India, which found topical natamycin 5 % to be superior to topical voriconazole 1 %, particulary for the treatment of Fusarium spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is no gold standard for the treatment of fungal keratitis [1,6], the combination of systemic voriconazole and topical natamycin seems to represent one of the most commonly used antifungal treatment regimens. This correlates with results of the MUTT 1 trial from South India, which found topical natamycin 5 % to be superior to topical voriconazole 1 %, particulary for the treatment of Fusarium spp.…”
Section: Discussionmentioning
confidence: 99%
“…Fungal Keratitis: A Six-Year Review at a Tertiary Referral Centre Pilzkeratitiden: ein 6-Jahres-Rückblick an einem tertiären Hornhautzentrum Background Fungal keratitis is relatively uncommon in developed countries [1], but it appears to have become more frequent in recent years with increasing proportions of filamentous fungi and an increasing percentage of contact lens usage as a predisposing factor [2]. In an earlier Swiss multicentre review, we reported a distinct increase in contact lens-associated Fusarium keratitis that might have occurred even before the Fusarium outbreaks in 2005 and 2006, respectively [3].…”
mentioning
confidence: 99%
“…(2,21) being the common pathogens. Current treatment for fungal keratitis is inadequate (8); thus, alternatives are needed.…”
mentioning
confidence: 99%
“…The Cochrane review8 in 2008 concluded that there was no evidence that the current available and investigational antifungal agents were effective. The review identified the need for large multicenter randomized trials.…”
Section: The Evidencementioning
confidence: 99%